Using multimodal information for the segmentation of fluorescent micrographs with application to Virology and microbiology - Held, Christian; Wenzel, Jens; Webel, Rike; Marschall, Manfred; Palmisano, Ralf; Wittenberg, Thomas; et al. (Proc*s 2011 Annual International Conference of the IEEE Engineering in Medicine and Biology Society,EMBC, 2011)
In order to improve reproducibility and objectivity of fluorescence microscopy based experiments and to enable the evaluation of large datasets, flexible segmentation methods are required which are able to adapt to different stainings and cell types. This adaption is usually achieved by the manual adjustment of the segmentation methods parameters, which is time consuming and challenging for biologists with no knowledge on image processing. To avoid this, parameters of the presented methods automatically adapt to user generated ground truth to determine the best method and the optimal parameter setup. These settings can then be used for segmentation of the remaining images. As robust segmentation methods form the core of such a system, the currently used watershed transform based segmentation routine is replaced by a fast marching level set based segmentation routine which incorporates knowledge on the cell nuclei. Our evaluations reveal that incorporation of multimodal information improves segmentation quality for the presented fluorescent datasets. © 2011 IEE
UnivIS-Import:2015-04-14:Pub.2011.med.IKMI.LHMMIPDR.usingm
Keywords: Fluorescence Microscopy; Digital Pathology; image analyis